Syphilis in Pregnancy: Profile and Associated Factors in the Northwest Region of São Paulo State - Garbin, Cléa Adas Saliba (2021)
Brazil is undergoing an epidemic of syphilis. In the pregnancy-puerperal cycle, syphilis has a high incidence and is considered a public health problem. This study aimed to perform the temporal and incidence analysis of gestational and congenital syphilis cases in 28 municipalities in the northwest region of the state of São Paulo. This was an observational, epidemiological, ecological study carried out with secondary data collected between 2010 and 2017 in public databases of SINAN and SINASC. The reported cases of gestational/congenital syphilis were described according to sociodemographic variables and chi-square association tests were applied at a significance level of 5%. There were 350 cases of gestational syphilis and 164 cases of congenital syphilis; the average vertical transmission rate was 44.09%; partners had low adherence to treatment; and 86.59% pregnant women attended prenatal care. It can be concluded that vertical transmission rate of syphilis is high, and few partners of pregnant women adhere to the treatment.